2009
DOI: 10.1097/brs.0b013e31818ff64e
|View full text |Cite
|
Sign up to set email alerts
|

O-C2 Angle as a Predictor of Dyspnea and/or Dysphagia After Occipitocervical Fusion

Abstract: The O-C2 angle has considerable impact on dyspnea and/or dysphagia after O-C fusion. The O-C2 angle is easily measured during surgery and can be a practical index with which to avoid postoperative dyspnea and dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
121
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 10 publications
7
121
0
1
Order By: Relevance
“…However, a study by Miyata et al [32] demonstrated an association between negative changes in the O/C2 angle after posterior cervical fusion surgery in RA patients with symptoms of dyspnea, dysphagia, or both. In a separate study reviewed above, improvement in the O/C2 angle after occipito-cervical fusion surgery in RA patients was associated with symptomatic improvement in patients with concomitant sleep apnea.…”
Section: Discussionmentioning
confidence: 97%
“…However, a study by Miyata et al [32] demonstrated an association between negative changes in the O/C2 angle after posterior cervical fusion surgery in RA patients with symptoms of dyspnea, dysphagia, or both. In a separate study reviewed above, improvement in the O/C2 angle after occipito-cervical fusion surgery in RA patients was associated with symptomatic improvement in patients with concomitant sleep apnea.…”
Section: Discussionmentioning
confidence: 97%
“…The range of motion (ROM) for each angle was defined as: the angle at extension -the angle at flexion. The difference in ROM for each angle was defined as: postoperative ROMpreoperative ROM [17]. Radiographic measurements were performed independently by three spine surgeons using institutional digital radiography software (Centricity Enterprise Web ver.3.0; GE Yokogawa Medical Systems, Tokyo, Japan).…”
Section: Assessment Of Neurologic and Radiographic Characteristicsmentioning
confidence: 99%
“…They found that a change in the O-C2 angle [ 10°is associated with narrowing of the oropharynx and postoperative dyspnea and dysphagia. 6 The measurements of our patient's O-C2 angle before and after halo fixation were 26.5°and 9.5°, respectively, for a reduction of 17°following application of the halo orthosis (Figs. 1a and 1b).…”
Section: Discussionmentioning
confidence: 72%
“…6 This is measured as the angle between McGregor's line (a straight line connecting the posterior edge of the hard palate to the most inferior tip of the occipital curve) and the line formed by the inferior endplate of the C2 vertebral body. Miyata et al compared changes in the O-C2 angle before and after occipitocervical fusion with an oropharyngeal cross-sectional area (measured from an axial view at the level of the tip of the epiglottis on a CT scan of the neck).…”
Section: Discussionmentioning
confidence: 99%